Problems of Big Data Adoption in the Healthcare Industries - Surya Kant Pal; Subhodeep Mukherjee; Manish Mohan Baral; Shilpee Aggarwal (ACHSM, 2021)
Big data offers the knowledge required for healthcare providers to streamline customer service processes that customize healthcare and create best practices for communicating with clients or patients. A more detailed and customized experience can be offered to customers. But there are many challenges that healthcare organizations are facing. The research aims to study big data challenges in the healthcare sector. A literature review is performed to discover big data problems in healthcare. A questionnaire is utilized for the survey research in the hospitals. Target populations are the staff who are working in the hospitals. For analysis, exploratory factor analysis is being performed. All the challenges are grouped into five factors. All the parameters are satisfied for the study. (*The paper was presented at the 2nd Conference on Business Data Analytics: Innovation in emerging trends in management data analytics. Apeejay School of Management, Dwarka, Delhi, India. November 2021)